The relationship of limited mobility of the cervical spinewith postural and mental reactions of students (Journal of Health Sciences, 2024)
Introduction: Previous studies have found that, in addition to the general factors for the occurrence of pain and reduced mobility of the cervical spine, the use of electronic devices promotes these, the excessive use of which can also lead to the occurrence of depressive symptoms in students. The aim of this study was to determine the mobility limitation of the cervical spine in students with reported neck pain, to determine the degree of disability and depression due to neck pain, to determine the correlation of mobility limitation of the cervical spine with the degree of disability and depression of students, and to determine the correlation of the degree of disability with the degree of depression.Methods: The research was conducted as a cross-sectional study from May to July 2021 at the University of Zenica in four faculties. The study used the General Questionnaire and two standardized questionnaires to assess disability due to neck pain (Index of Disability due to Neck Pain) and the degree of depression (patient health questionnaire).Results: A total of 147 students with reported neck pain participated in the study. A limitation of mobility was found in 30.6% of the students in flexion, 25.2% in rotation, 23.8% in lateral flexion, and 20.4% on extension. Mild disability due to neck pain was found in 58.5% of students, moderate in 23.8%, and severe in 2.7%. 45.6% of the students had mild depression, 18.4% had moderate depression, and 5.4% had severe depression.Conclusion: Restricted flexion and rotation are more common than restricted lateral flexion and extension of the cervical spine. About half of the students who reported neck pain had a mild degree of disability and mild depression. A strong positive correlation was found between the degree of disability and depression in students with neck pain.